Habitação progressiva autoconstruída: caracterização morfológica com uso da gramática da forma - Mororó, Mayra Soares de Mesquita (2012)
This paper concerns the spontaneous habitation focused on the progressive production processes of housing. It considers as problematic the relative scarcity of studies on that subject, particularly in relation to the emergent typologies of self-construction processes. Therefore, it was developed a case study in the Planalto Pici – a Special Zone of Social Interest (ZEIS) in Fortaleza, capital of the state of Ceará, Brazil – applied from a methodological arrangement involving the physical measurements and registration of progressivity in the construction of 94 houses. This information was examined and described by adopting the shape grammar - analysis tool created by Stiny and Gips in the 70s - as an instrument of representation of logic that involves the formation of units. From the data collected, we sought for recurrences of forms, in order to understand the morphological characteristics of dwellings in line with research on type, according to the definition of Rossi and Argan. The results indicate a multiplicity of factors involved in the production of autonomous housing and point to the need for research focusing on these specific fragments of the city, considering that understanding the morphology requires an understanding of the urban context. Based on the knowledge attained, the research contributes a method that speculates on future forms, and an overview of knowledge about the user, which may indicate a path for the development of housing design projects best suited to the needs of the public as well as to grant in technical assistance programs applied to the study environment.